Implementação de técnicas de motivação no Moodle IMD - Araújo, Tadeus Lima de (2017)
Moodle is a virtual learning environment (VLE) that was created in the year of 2001 as an open-source alternative for a distance education environment. It is used in Instituto Metrópole Digital since it's foundation, in February of 2010. Inside the system there are some features that allow the users to interact with each other. One of them is the forum feature, which are created by the courses and classes professors and/or tutors of the institution's technical courses. Although this feature exists, it was noticed that the students rather use external applications like instant messengers than use Moodle built-in features. From that came the need to engage the students to use the forum features in Moodle. This project’s goal is to implement and deploy two motivation techniques: one of social recognition, as reaction buttons inside Moodle's forum feature, and a gamification one, which converts the reactions received by the users as points to a competition in a ranking inside the system. In addition, SQL queries to extract data for the analisis of the impact of the implemented techniques.